2015
DOI: 10.1530/eje-15-0130
|View full text |Cite
|
Sign up to set email alerts
|

Median-lower normal levels of serum thyroxine are associated with low triiodothyronine levels and body temperature in patients with central hypothyroidism

Abstract: Objective: Although it has been recommended that serum free thyroxine (FT 4 ) levels should be targeted to middle-upper normal levels during levothyroxine (L-T 4 ) replacement therapy in patients with central hypothyroidism (CeH), the rationale has not been clarified. Methods: A retrospective single-center study enrolled 116 patients with hypothyroidism (CeH, nZ32; total thyroidectomy (Tx), nZ22; primary hypothyroidism (PH), nZ33; and control benign thyroid nodule (C), nZ29). The patients had received L-T 4 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…In central hypothyroidism and total thyroidectomy, patients with medianlower normal levels of serum FT 4 exhibited lower serum FT 3 levels and lower body temperature. These results support the association with body temperature and serum T 3 levels to T 4 in patients with central hypothyroidism and total thyroidectomy [16]. Athyreotic patients who have undergone a total thyroidectomy live in a chronic state of abnormal thyroid hormone status for the remainder of their lives.…”
Section: Discussionsupporting
confidence: 81%
“…In central hypothyroidism and total thyroidectomy, patients with medianlower normal levels of serum FT 4 exhibited lower serum FT 3 levels and lower body temperature. These results support the association with body temperature and serum T 3 levels to T 4 in patients with central hypothyroidism and total thyroidectomy [16]. Athyreotic patients who have undergone a total thyroidectomy live in a chronic state of abnormal thyroid hormone status for the remainder of their lives.…”
Section: Discussionsupporting
confidence: 81%
“…Hirata et al studied patients with central hypothyroidism and athyreotic patients who underwent total thyroidectomy. In central hypothyroidism and total thyroidectomy patients, those with median-lower to normal levels of serum fT4 exhibited lower serum fT3 levels and lower body temperature (25). These data support an important role of serum fT3 levels in the manifestation of symptoms, which has implications for clinical decision making on dose adequacy, particularly in athyreotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of FT4 acquires a more relevant role in the evaluation of replacement therapy than in primary hypothyroidism. Several groups [49,56,58,60] reported that concentrations of FT4 in the upper part of normal range might represent an appropriate target in most treated CeH patients (Recommendation 26).…”
Section: How Should Ceh Patients Be Managed and Treated?mentioning
confidence: 99%